The Litigators - Grisham, John (London Hodder & Stoughton, 2011)
Law firm partners Oscar Finley and Wally Figg see a chance for huge financial gain when they learn of a pending class action lawsuit against the makers of Krayoxx, a popular cholesterol-reducing drug suspected of causing heart attacks.
Keywords: Class actions (Civil procedure) -- Products liability--Drugs -- Illinois--Chicago